Participation of genes involved in the process of anaerobic respiration of infection in chickens by Salmonella Typhimurium - Arguello, Yuli M. S.; Paiva, Jacqueline B. de; Penha Filho, Rafael A. C.; Berchieri Junior, Ângelo (Brazilian Journal of Veterinary Pathology, 2010)
Intestinal pathogens are exposed to various stress conditions during their infectious cycle. Anaerobiosis, one of such hostile condition, is offered by the host within gut and intestinal lumen, where survival, multiplication and entry into intestinal epithelial cells are priority for the invasion of the pathogen. The fumarate reductase (frdABCD), dimethyl sulfoxide (DMSO)-trimethylamine N-oxide (TMAO) reductase (dmsABC), and nitrate reductase (narGHIJ) operons in Salmonella Typhimurium (STM) encode enzymes involved in anaerobic respiration to the electron acceptors fumarate, DMSO, TMAO, and nitrate, respectively. They are regulated in response to nitrate and oxygen availability and changes in cell growth rate. Vitamin B12 (cobalamin) is synthesized by Salmonella Typhimurium only under anaerobic growth conditions used as a cofactor in four known reactions. The deletion of cobS and cbiA genes prevent any form of cobalamin production. In the present study we evaluate the infection of birds by mutants of STM, with the anaerobic respiratory system committed by mutations in the genes: narG, napA, cobS, cbiA, frdA, dmsA, and torC. Virulence was assessed by oral inoculation of groups of one-day-old broilers with 0.1 mL of culture contained 108 colony forming units (CFU)/mL or diluted at 10-3 and 10-2 of strains mutants of Salmonella Typhimurium. Clinical signs and mortality were recorded over a period of 21 days. In general, the symptoms of chickens infected with the mutant strains were similar to those presenting by control birds. Except for STMNalr delta-cbiA, all showed reduced capacity to cause mortality in comparison with the original strain. The mortality of group of chickens infected with STMNalr delta-narG, STMNalr delta-frdA, STMNalr delta-dmsA and STMNalr delta-cobS delta-cbiA showed significant decrease in mortality compared to control group (p<0.05).